Phase Unwrapping for Multiple Interferograms: An Airborne Experiment for TanDEM-X - Andres, Christian; Scheiber, Rolf; Bachmann, Markus; Hueso-Gonzalez, Jaime; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
This paper describes a joint phase unwrapping approach for multiple interferograms acquired on different trajectories. The work done here was carried out for purposes of TanDEM-X [1] simulations, using the experimental airborne Radar System (E-SAR) of the German Aerospace center. The results are validated using ICE-SAT data takes.
DLR Import::2019-04-03